Hypothyroidism impairs the circadian rhythmicity of clock genes and proteins involved in gut nutrient absorption in female mice - Ayla Secio-Silva; Paulo Henrique Evangelista-Silva; Felipe Emrich; Letícia Selvatici-Tolentino; Maíza Ferreira; Ana Bárbara de Paula Silva; Bruno Henrique Gomes; Tatienne Neder Figueira-Costa; André Gustavo Oliveira; Rodrigo Antonio Peliciari-Garcia; Francemilson Goulart-Silva; Paula Bargi-Souza (Frontiers in Physiology)
Hypothyroidism is a common thyroid dysfunction with a higher prevalence in women. Impairments in the regulation of basal metabolism, small intestine nutrient transporter, dyslipidemia, and disruption in circadian clocks have been associated with the thyroid disorder. This study aimed to evaluate whether hypothyroidism affects the small intestine circadian clock and the daily expression pattern of gut nutrient transporters in female mice. Adult female C57BL/6J mice were subjected to hypothyroidism by the administration of methimazole (0.1%) and sodium perchlorate (1%) in drinking water for 45 days. After, the animals were subdivided and euthanized every 4 h over the 24 h period under deep anesthesia. The proximal small intestine segment was collected and immediately frozen for gene expression analysis of circadian core clock components (Bmal1, Per2, Cry1, and Nr1d1) and nutrient transporters by RT-qPCR. The daily protein content of nutrient transporters involved in the absorption of the products of hydrolysis of lipids, proteins, and carbohydrates was evaluated over 24 h in isolated small intestinal epithelium by Western blotting. The expression of clock genes and protein content of nutrients transporters in the jejunum of control female mice exhibited a well-defined circadian rhythmicity, while no rhythmic oscillation over 24 h was observed for the transporter transcripts. Hypothyroidism abolished the circadian rhythmicity of circadian clock, punctually reduced the transcript content of Slc2a5 (GLUT5) at ZT12 and Slc2a2 (GLUT2) at ZT4, and disrupted the circadian oscillation of L-FABP, CD36, PEPT1, and GLUT2 protein contents in the small intestine of female mice. In conclusion, our findings indicate that thyroid hormones modulate the circadian clock of small intestine and the daily rhythmicity of components related to absorptive processes in female mice. Moreover, our data suggest that the mechanisms triggered by thyroid hormones involve posttranscriptional and/or translational modifications of proteins related to lipid, protein, and carbohydrate absorption. Together, these data contribute to the general comprehension of metabolic alterations often observed in hypothyroidism and have far-reaching implications at clinical levels considering the higher worldwide prevalence of hypothyroidism in women and its association with obesity and metabolic syndrome.